The Education of Economists: A Different Perspective - Bateman, Bradley W. (Journal of Economic Literature, 1992)
Suddenly, and somewhat unexpectedly, there seems to be a real chance for change in the way economics is taught in American colleges and universities. During the last two years, three different groups have taken a critical look at economics education and declared that change is in order. The Association of American Colleges (AAC), in conjunction with the American Economic Association (AEA), commissioned a study of the undergraduate economics major which has led to a report with several recommendations for reform (John Siegfried et al. 1991); in response to a National Science Foundation (NSF) symposium that revealed concern over the state of graduate education, the AEA formed the Commission